2014
DOI: 10.1021/jf501024j
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Irradiation Induced Changes in Protein Molecular Structures of Barley Grains: Relationship to Changes in Protein Chemical Profile, Protein Subfractions, and Digestion in Dairy Cows

Abstract: The objectives of this study were to evaluate microwave irradiation (MIR) induced changes in crude protein (CP) subfraction profiles, ruminal CP degradation characteristics and intestinal digestibility of rumen undegraded protein (RUP), and protein molecular structures in barley (Hordeum vulgare) grains. Samples from hulled (n = 1) and hulless cultivars (n = 2) of barley, harvested from four replicate plots in two consecutive years, were evaluated. The samples were either kept as raw or irradiated in a microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Heat processing alters EDDM of protein feeds by altering the protein molecular structures, such as the uncoiling of pleated structures or denaturation of the whole protein molecules. These heat-induced structural changes expose the intact AA, and subsequently results in the development of cross-linkages among peptides/AA, and between AA and carbohydrates (Yan et al, 2014). Both temperature and duration of heating play a key role in the level of denaturation and development of cross linkages, and hence the protection of feed against rumen degradation (Khan et al, 2015).…”
Section: Pelleting-induced Changes In In Situ Degradation Kinetics Ofmentioning
confidence: 99%
“…Heat processing alters EDDM of protein feeds by altering the protein molecular structures, such as the uncoiling of pleated structures or denaturation of the whole protein molecules. These heat-induced structural changes expose the intact AA, and subsequently results in the development of cross-linkages among peptides/AA, and between AA and carbohydrates (Yan et al, 2014). Both temperature and duration of heating play a key role in the level of denaturation and development of cross linkages, and hence the protection of feed against rumen degradation (Khan et al, 2015).…”
Section: Pelleting-induced Changes In In Situ Degradation Kinetics Ofmentioning
confidence: 99%
“…The use of heat exchangers in continuous conventional systems has been shown to lead to minimum damage on the nutritional components in milk when mild temperatures are used (e.g., HTST), in comparison with a batch system. In addition, the use of microwaves, for example, was shown to change protein conformation and cross‐linkages between amino acids and reducing sugars such as during Maillard reactions in a time–temperature‐dependent manner (de Pomerai et al, ; Yan, Khan, Zhang, Yang, & Yu, ). In summary, the type of heating system (i.e., continuous heat exchanger, batch system, or incidence of microwaves) has a key impact on the preservation of milk antimicrobial proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, sample preparation was reported as: Grains from two newly‐developed hulless cultivars ( CDC‐Fibar and HB08302 ) with an altered carbohydrate composition (amylose/amylopectin ratio in β‐glucan) and a normal hulled cultivar (CDC Copeland ) of barley were evaluated. The samples were provided by Aaron D. Beattie (Crop Development Center, University of Saskatchewan, Saskatoon, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has reported that barley is primarily used as an energy source in dairy cow rations. However, hulless barley rapidly and extensively degrades in the rumen, resulting in a lower rumen undegraded protein value .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation